Infliximab Biosimilars: A Promising but Unusual Treatment for Mycobacterial Immune Reconstitution Inflammatory Syndrome in Human Immunodeficiency Virus-Infected Patients. (7th August 2017) - Troya, Jesús; Cuevas, Guillermo; Ryan, Pablo; Díez, Victorino; Izquierdo, Elsa; Escobar, Ismael; Solís, Javier
Abstract: Immune reconstitution inflammatory syndrome can present as a paradoxical reaction after initiation of antiretroviral treatment in patients with severe immunosuppression and underlying infections. Immune reconstitution inflammatory syndrome has often been associated with mycobacteria, and the clinical response to traditional treatment with corticosteroids is not always satisfactory. Consequently, administration of an infliximab biosimilar could lead to an improvement in the clinical status of these patients.